Upconverting nanoparticles in bioaffinity assays : new insights and perspectives - Lahtinen, Satu (fi=Turun yliopisto|en=University of Turku|, 2019)
Photon upconverting nanoparticles (UCNPs) are promising reporters for supersensitive bioaffinity assays because they can be detected completely without autofluorescence background. This is enabled by anti-Stokes shifted luminescence where low-energy infrared radiation is converted to high-energy emission at visible wavelengths. Because the excitation and emission are at an optical window for biomaterials, UCNPs can be detected even in challenging sample materials such as whole blood. However, wider use of UCNPs in bioaffinity assays is limited due to certain challenges. Recently, there has been ongoing studies on UCNP structural integrity and luminescence in water and the effect of surface modification to biomolecule interactions, which should still be studied further in order to use the full potential of UCNPs in bioaffinity assays. The aim of this thesis was to study the applicability of UCNP reporters in sensitive homogeneous and heterogeneous bioaffinity assays. The applicability of UCNPs to homogeneous assays was demonstrated by introducing Eu3+ chelate as an acceptor in an upconversion resonance energy transfer based assay. The Eu3+ chelate’s intrinsic luminescence lifetime was longer than that of the UCNP donor and therefore the sensitized acceptor emission could be measured even after the donor’s luminescence had decayed resulting in higher signal-to-background ratios. Additionally, the potential of UCNPs as reporters for cross-correlation spectroscopy was demonstrated with a homogeneous sandwich immunoassay. The assay was based on simultaneous detection of two differently emitting UCNPs brought together by binding of an analyte. UCNPs would be suitable reporters for cross-correlation spectroscopy applications where traditional fluorescence reporters suffer from autofluorescence. One of the major factors limiting the immunoassay sensitivity is non-specific binding of UCNP conjugates. In this thesis, the non-specific binding of poly(acrylic acid) (PAA)-functionalized UCNP conjugates was reduced significantly in heterogeneous sandwich immunoassays by adding free PAA to the buffer during reporter incubation. The free PAA most likely blocked those areas in solid support where the UCNP conjugate might have bound non-specifically. The reduction in non-specific binding enabled detection of three and half times lower analyte concentration demonstrating that high sensitivity assays can be achieved with UCNP reporters. In addition, the ion dissolution from fluoride-based UCNPs and its effect on luminescence and structural integrity of nanoparticles was studied in water-based solutions. The ions were found to dissolve until solubility equilibrium was achieved and the fluoride ions were observed to have major impact on the dissolution. The UCNPs disintegrated completely in highly diluted suspensions resulting in the disappearance of luminescence. The ion dissolution was prevented by adding free fluoride ions to the solution, which was an important observation in order to use diluted UCNP concentrations in bioaffinity assays. The study also demonstrated the requirement for surface capping that would protect the UCNPs from environmental effects.

Käänteisviritteiset nanopartikkelit soveltuvat leimoiksi erittäin herkkiin bioaffiniteettimäärityksiin, koska niiden fotoluminesenssi voidaan havaita täysin ilman mittausta häiritsevää autofluoresenssia. Tämä perustuu käänteisviritteisten partikkelien Stokesin siirtymän vastaiseen fotoluminesenssiin, jossa matalaenergineninfrapunasäteily muutetaan korkeanergiseksi emissioksi näkyvillä aallonpituusalueilla. Käänteisviritteisiä nanopartikkeleita voidaan erityisesti käyttää hankalissa näytemateriaaleissa kuten kokoveressä, koska niiden viritys ja emissio tapahtuvat biomateriaaleille optisesti läpinäkyvillä alueilla. Kuitenkin käänteisviritteistennanopartikkelien ominaisuuksia vesiliuoksissa sekä niiden pintamodifikaation vaikutusta vuorovaikutukseen biomolekyylien kanssa tulisi tutkia lisää, jotta niitä voitaisiin käyttää laajemmin bioanalyyttisissä sovelluksissa. Väitöskirjan tarkoituksena oli tutkia käänteisviritteisten nanopartikkelien soveltuvuutta leimoiksi herkkiin homogeenisiin ja heterogeenisiin bioaffiniteettimäärityksiin. Soveltuvuutta homogeenisiin määrityksiin tutkittiin resonanssienergiansiirtoon perustuvassa määrityksessä, jossa Eu3+-kelaatti oli energian vastaanottaja. Eu3+-kelaatin luontainen elinikä on pidempi kuin energian luovuttajana toimivan käänteisviritteisen nanopartikkelin, mikä mahdollisti vastaanottajan herkistetyn emission mittaamisen sen jälkeen, kun luovuttajan emission oli sammunut. Lisäksi käänteisviritteisten nanopartikkelien soveltuvuus ristikorrelaatiospektroskopiaan osoitettiin kehittämällä kaksipuoleinen homogeeninen määritys, joka perustui kahdella eri aallonpituudella emittoivaan käänteisviritteiseen nanopartikkelin samanaikaiseen havainnointiin analyytin läsnä ollessa. Erityisesti nanopartikkelikonjugaattien epäspesifinen sitoutuminen rajoittaa alhaisten analyyttipitoisuuksien havainnointia bioaffiniteettimäärityksissä. Väitöskirjassa polyakryylihappolla pinnoitettujen käänteisviritteisten nanopartikkelien epäspesifistä sitoutumista vähennettiin merkittävästi kaksipuoleisissa heterogeenisissa määrityksissä lisäämällä leimapuskuriin vapaata polyakryylihappoa. Tämä mahdollisti kolme ja puoli kertaa matalampien analyyttipitoisuuksien havaitsemisen, mikä on esimerkkinä käänteisviritteisten nanopartikkelien soveltuvuudesta leimoiksi erittäin herkkiin määrityksiin. Lisäksi väitöskirjassa tutkittiin fluoripohjaisten käänteisviritteisten nanopartikkelien ionien liukenemista vesiliuoksissa ja sen vaikutusta nanopartikkelin rakenteen ehjyyteen ja luminesenssiin. Tutkimuksessa havaittiin, että ionien liukeneminen perustui liukoisuustuloon, mihin fluorilla oli erittäin suuri vaikutus. Erityisesti alhaisissa pitoisuuksissa käänteisviritteiset nanopartikkelit hajosivat melkein kokonaan, minkä vuoksi myös luminesenssia ei juuri enää havaittu. Ionien liukeneminen nanopartikkeleista voitiin kuitenkin estää lisäämällä liuokseen vapaata fluoria. Tämä havainto edistää käänteisviritteisten nanopartikkelien käyttämistä sovelluksissa, joissa tarvitaan alhaisia nanopartikkelin pitoisuuksia.